2019
DOI: 10.1128/iai.00145-19
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia muridarum Induces Pathology in the Female Upper Genital Tract via Distinct Mechanisms

Abstract: Sexually transmitted infection with Chlamydia trachomatis may lead to fibrotic blockage in women's upper genital tracts, resulting in tubal infertility. Intravaginal inoculation with C. muridarum readily induces fibrotic blockage or hydrosalpinx in mice and is used for investigating C. trachomatis pathogenicity. Using this model in combination with an antibody depletion approach, we confirmed CD4 ϩ T cell-mediated protective immunity and a CD8 ϩ T cell-dependent pathogenic mechanism during chlamydial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…While CD4 ϩ T cells are necessary for Chlamydia clearance (5,22), antigen-nonspecific bystander CD4 ϩ T cells have been found to contribute to immunopathology in mice infected with C. trachomatis serovar D (23). Furthermore, it has been recently demonstrated that CD4 ϩ T cells can induce pathology in mice deficient in CD8 ϩ T cells, following C. muridarum infection (24). It is possible that the influx of CD4 ϩ T cells to the upper genital tract in mice following transcervical infection contributes not only to IFN-␥ production but also to immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…While CD4 ϩ T cells are necessary for Chlamydia clearance (5,22), antigen-nonspecific bystander CD4 ϩ T cells have been found to contribute to immunopathology in mice infected with C. trachomatis serovar D (23). Furthermore, it has been recently demonstrated that CD4 ϩ T cells can induce pathology in mice deficient in CD8 ϩ T cells, following C. muridarum infection (24). It is possible that the influx of CD4 ϩ T cells to the upper genital tract in mice following transcervical infection contributes not only to IFN-␥ production but also to immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…To quantitate live chlamydia, each swab was soaked in 0.5 ml of SPG buffer and vortexed with glass beads, and the chlamydial organisms released into the supernatants were titrated on HeLa cells. The infected cultures were processed for immunofluorescence assay as described previously [ 15 ]. A rabbit antibody (designated R1604, raised against purified C. muridarum EBs) was used as a primary antibody to label C. muridarum in HeLa cells and was then visualized with goat anti-rabbit IgG conjugated with Cy2 (green; Solarbio, SE131).…”
Section: Methodsmentioning
confidence: 99%
“…1. We have previously demonstrated that CD4 ϩ T cells are able to mediate chlamydial pathogenicity in CD8 KO mice (24). Interestingly, following adoptive transfer with CD8 ϩ T cells from OT1 mice, the recipient CD8 KO mice were no longer able to develop significant hydrosalpinx.…”
Section: Figmentioning
confidence: 97%
“…It is now recognized that clearance of chlamydial colonization from both genital (8) and small intestinal (23) mucosal tissues is dependent on Chlamydia-specific CD4 ϩ Th1 immunity. Besides a dominant role in protective immunity, CD4 ϩ T cells may also contribute to chlamydial pathogenicity under certain conditions, for example, in CD8 knockout (KO) mice (24). However, in most cases, CD8 ϩ T cells play a more dominant role in chlamydial pathogenesis since antibody depletion of CD8 ϩ T cells from wild-type C57BL/6J mice significantly reduced pathology induced by C. muridarum (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation